Peningkatkan Perekonomian Masyarakat Dengan Mengembangkan Ekowisata Berbasis Kearifan - Candra Hidayat; Riza Weganova; Ayu Liskinasih (Jurnal Pemberdayaan Masyarakat, 2023)
Jenggolo Village is one of the villages in Malang Regency. The number of people aged 20-59 who have not worked is 430 people from the total workforce of around 2382 people. Jenggolo Village has ecotourism potential in the form of Sumber Songo and heritage sites of the Jenggolo Kingdom. This study aims to develop ecotourism based on local wisdom to improve the economy of the community in Jenggolo Village. Development will focus on improving ecotourism governance, marketing Sumber Songo and royal sites, creating accountable and transparent financial audits, establishing conservation mechanisms, and increasing community involvement, both in conservation and economic activities. This study also aims to develop a participatory and collaborative learning model between students, lecturers, communities and village officials in managing ecotourism sites. The research method used is a qualitative method which includes the stages of action research, formulation of village policies, and development research. At the action research stage, problem analysis will be carried out, business strategy design through the Business Model Canvas, implementation and evaluation will be carried out. Then proceed with the formulation of village policies and the last stage is the creation of learning models MBKM.